ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI PADA DINAS SOSIAL, TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SIGI - Affandy, Affandy (Katalogis, 2016)
This research aims at finding out the influence of leadhership style toward the motivation of the employees at social department of labor and transmigration Sigi regency. This was a qualitative research. The informans were taken based on the criteria: authorities, engaged or undergoing the process of leadhership toward the motivation. The data were collected through observation, interview, and documentation. The result of analysis show that motivation of the employees at social department of labor and transmigration Sigi regency was a partisipative leadhership style. This type of leadhershipstyle can give goodcooperation between the leader and the employees and the cooperation among employees. It can be seen from the way the employees consult their job to their leader, the leader’s way to take a decision, how the leader delegates the authority to employees, and the way the leader gives an apportunity to the employees to express their opinion, ideas about their activites nd job. By applying a pertisipative leadhership style, the head of social department of labor and transmigration can improve the motivation of the employees by providing a comfort atmoshere and giving confidence and responsibility in doing the job.